PENGARUH KEPEMILIKAN PUBLIK, LIKUIDITAS, KOMITE AUDIT, DAN REPUTASI KANTOR AKUNTAN PUBLIK TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN - Fadjar Harimurti, Antyanta Wahyu Hendiyantyo, Djoko Kristianto (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2018)
The financial statements are records of corporate financial information during an accounting period that can be used to describe a company's performance. Companies that go public have an obligation to deliver audited financial statements in a timely manner.This study aims to analyze the factors that affect the timeliness of the delivery of financial statements. These factors are public ownership, liquidity, audit committee, and reputation of public accounting firm.This research is a survey research on 39 manufacturing companies of special industrial sector listed on Indonesia Stock Exchange (IDX) period 2015 and 2016. Quantitative data type and data collection technique using secondary data. Sampling technique with purposive sampling. Hypothesis test using logistic regression analysis.The result of logistic regression analysis shows that public ownership, liquidity, audit committee, and reputation of public accountant firm have effect but insignificant effect on the timeliness of financial reporting at various industry manufacturing companies listed on Indonesia Stock Exchange in 2015 and 2016.Keywords: timeliness of financial statement submission, public ownership, liquidity, audit committee, KAP reputation.